2008
DOI: 10.2139/ssrn.1016904
|View full text |Cite
|
Sign up to set email alerts
|

Hedge Fund Due Diligence: A Source of Alpha in a Hedge Fund Portfolio Strategy

Abstract: Due diligence is an important source of alpha in a well designed hedge fund portfolio strategy. It is generally understood that the high returns possible in investing in hedge funds are somewhat offset by the relative lack of transparency on operational issues. The performance of a diversified hedge fund portfolio can be enhanced by excluding those funds likely to do poorly -or fail -due to operational risk concerns. However, effective due diligence is an expensive concern. This implies that there is a strong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
30
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 23 publications
5
30
0
1
Order By: Relevance
“…Brown, Fraser, and Liang (2008) argued that effective due diligence is a source of hedge fund alpha. They found that large funds of funds (FoFs) can absorb the fixed costs associated with due diligence.…”
mentioning
confidence: 99%
“…Brown, Fraser, and Liang (2008) argued that effective due diligence is a source of hedge fund alpha. They found that large funds of funds (FoFs) can absorb the fixed costs associated with due diligence.…”
mentioning
confidence: 99%
“…In recent research, Brown, Fraser, and Liang (2007) argue that effective due diligence is a source for hedge funds alpha. They find that large funds of funds have the capability of absorbing the fixed costs associated with due diligence.…”
mentioning
confidence: 99%
“…As documented in the hedge fund literature, fund size, fee structure, and high watermark typically have important influence on hedge fund performance (see, e.g., Ackermann et al, 1999;Naik, 2000, 2004;Agarwal et al, 2009;Baquero et al, 2005;Brown et al, 1999Brown et al, , 2001Brown et al, , 2008Brunnermeier and Nagel, 2004;Cremers et al, 2005;Edwards and Caglayan, 2001;Getmansky et al, 2004;Liang, 1999Liang, , 2000. We control for these known effects in our empirical analyses.…”
Section: Data and Sample Characteristicsmentioning
confidence: 99%